Evaluating of IT Services on Accurate Application Using COBIT 5 (Case Study : PT. SS Dinamika) - Calvin Tjee; Kevin Christianto (Maranatha University Press, 2018)
PT. SS Dinamika is a company engaged in marketing umbrella throughout Indonesia to meet customer’s demand. Places that have been marketed and still making orders are Medan, Sumatera, and Palembang. This company has implemented an Information System specifically Accurate Accounting Software to support the company’s business processes. Unfortunately, the problem arises where the company experiences a delay in entering sales data because the administration has not fully mastered the application. The company’s IT condition has never been measured and audited. Therefore, an audit measurement is needed to measure the company’s business processes, applications, and corporate strategy. In this audit, the measurement uses the framework of COBIT 5 which is focused on the DSS01, DSS02 and DSS04 domain (Deliver, Service and Support). The result of this research after analyzing the data is the value of Capability Level on DSS01, DSS02 and DSS04 are at level 1 (Performed Process) and the Expected Level are at level 3. The conclusion of this research is the company has already run its business process pretty well. Unfortunately, the company still has to make some improvements on each DSS domain that has been analyzed.